The use of mononuclear and multinuclear complexes of rhodium and ruthenium in catalytic olefin hydroformylation and hydroaminomethylation reactions - October, Jacquin (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.